The disability from the perspective of university students and its implications - Leite, Lucia Pereira [UNESP]; Mattos, Beatriz Marques de; Feitosa de lacerda, Cristina Broglia (Centro Espanol Documentacion Discapacidad-cedd, 2023)
The phenomenon of disability is multidetermined, and it can be explained in different ways, implying understanding it for different causes. The objective of this research was to identify and analyze how university students position before utterances which treats about different disability conceptions. A total of 1,472 students from courses in the Biological, Exact and Human areas of a public university in the State of Sao Paulo, Brazil. The Scale for Conception of Disability (SCD) was virtually applied. The findings indicate that most respondents are in favor of questions that show social and historical-cultural conceptions to understand the disability. This is considered a positive fact, as the way in which the subject conceives certain knowledge indicates the way of dealing with the object, in this case, in relation to a population segment that is still, frequently, in a situation of social exclusion. Valuing human differences in Higher Education, proposing actions to value differences with future professionals, becomes the outcome of this research, in the promotion of a more egalitarian society.
Keywords: Disabled persons; scale; higher education; Psychology